Health of trees in Titiwangsa Recreational Park, Kuala Lumpur, Malaysia - Badrulhisham, Norainiratna; Mariapan, Manohar; Mohamad Kasim, Mohamad Roslan (Penerbit Universiti Malaysia Terengganu, 2013)
Trees are very important element in the construction of garden and landscape area. The health status of trees in urban park has not been studied compared to roadside trees. This research was conducted to access the health of trees in Titiwangsa Recreational Park in Kuala Lumpur, Malaysia. A random sample selection of trees assessed in Titiwangsa Recreational Park for health status using Tree Health form as the primary instrument. The results showed that trees in Titiwangsa Recreational Park were in fair (63.1%) to good (30.4%) health status. Only less than 6.6% with poor (6.3%) and dead tree (0.2%) indicates that most of the trees in study area suffered from many structural and mechanical damage, poor crown health and have poor vigor.